STATUS SOSIAL EKONOMI SEBAGAI FAKTOR RISIKO KEJADIAN OBESITAS DI KABUPATEN BANYUMAS - Mulyanto, Joko; Darmawan, Anton B (MANDALA of Health, 2014)
Obesity is a significant global and national health problem, and has declared by WHO as global epidemic.The prevalence of obesity in developed and mostly developing countries has dramatically increased during the last decade. Socio-economic status has been identified as one of significant predictors of obesity.Â  However, studies in different countries showed various result regarded the relationship between socioeconomic status and obesity. The study objective was to identify socio-economic status as an risk factor of obesity at Banyumas District. This study was a secondary analysis with cross-sectional approach using the data from Riset Kesehatan Dasar 2007 at Banyumas District. Samples of study were 1827 adult household members represented the residence of Banyumas District. The main independent variable was socioeconomic status measured by the quintile of income. The dependent variable was obesity measured by BMI with cut of point 27kg/m2. The confounding variabeles controlled by study were gender, age, marital status, employment, geographical location, and physical activity.Â  Data analyzed by multivariate analysis using multiple logistic regressions and stratification analysis by gender. Study result showed that the prevalence of obesity at Banyumas District is 22,3% for total sample of the study, while by gender the prevalence of obesity is 14,8 % for male and 29,1% for female respectively. After adjusted for confounding variables, socioeconomic status was risk factor of obesity at Banyumas District with OR 1,57 (95%CI:1,07-2,29) at 5th income quintile. For the male respondents, socioeconomic status has the OR 2,55 (95%CI, 1,29-5,0) at 5th income quintile. These results showed that the prevelance of obesity at Banyumas District was relatively high, and higher socioeconomic status significantly increased the odd of becoming obese.